Epidemiology of trypanosomal infections in caprine in Medallo area of the Ghibe Valley, south west Ethiopia - Mulugeta, B. (Mekelle University, 2010)
Trypanosomosis is one of the major diseases hindering livestock production in Africa. Many studies have been carried out on the prevalence of the disease in cattle but very little has been done in small ruminants. A Cross sectional epidemiological survey of Caprine trypanosomosis was conducted from November 2009 to March 2010 in Nono district, Medallo area at Ghibe research site of the International Livestock Research Institute (ILRI), southwest Ethiopia, to investigate the existence and prevalence of Caprine trypanosomosis on the study area. A total of 400 blood samples were collected and the blood films were examined by Buffy coat technique for the detection of trypanosomes. The study conducted on 400 goats revealed that 4 (1%) of the goats were found to be infected with trypanosomes. Up on examination on thin smears of infected blood, Trypanosome congolense was the only species found. Infection rate of age, sex, color and body condition scoring did not reveal significant difference (P>0.05). Thus based on the findings of the study some recommendations were forwarded aiming at the attentions to be given in the prospect of the disease in the small ruminants in the country.